Influence of the intertropical convergence zone on early cretaceous plant distribution in the South Atlantic - Carvalho, Marcelo de Araujo; Lana, Cecilia Cunha; Sa, Natalia P.; Santiago, Gustavo; Giannerini, Michelle C. S.; Bengtson, Peter (Scientific reports, 2022)
The influence of the Intertropical Convergence Zone (ITCZ) in the emerging South Atlantic region during the late Aptian (Early Cretaceous) is reflected in the spatio-temporal distribution of plant communities recorded in eight Brazilian sedimentary basins. The distribution of the bioclimatic groups of hygrophytes, hydrophytes, tropical lowland flora, upland flora, and xerophytes was quantified using pollen and spores. A predominance of xerophytes from the tropical xerophytic shrubland biome characterized the pre-evaporitic, evaporitic, and post-evaporitic paleoclimatic phases, in particular the evaporitic phase. The region experienced humidity events in the pre-evaporitic and post- evaporitic phases, especially near the paleoequator, where the tropical rainforest biome with two phytophysiognomies (lowland and montane rainforests) prevailed. Increasing humidity had a positive effect on plant diversity.
Gesehen am 09.11.2022